Boosting the Usage of Green Energy for EV Charging in Smart Buildings Managed by an Aggregator through a Novel Renewable Usage Index - Guzman, Cindy P. [UNESP]; Arias, Nataly Banol [UNESP]; Franco, John Fredy [UNESP]; Soares, Joao; Vale, Zita [UNESP]; Romero, Ruben [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
The growing trend of electric vehicles (EVs) and building integrated photovoltaics (BIPVs) is a promising means to reduce related climate change issues. EV loads can be managed via an aggregator to maximize the usage of green energy produced by photovoltaic units (PV) through smart charging strategies that exploit controllable EV demand connected to BIPV. Previous works have focused on the EV charging coordination in a smart BIPV, although without an optimization that encourages EV charging with the energy produced by the PV units. This paper proposes an aggregation strategy that maximizes a green energy index (GEI) for the smart charging coordination of EVs, which takes advantage of periods with high PV availability to charge the EV batteries; moreover, a post-processing stage for the GEI provides EV owners with information about the percentage of charged energy, period by period, that comes from PV generation. The results for a case study with 510 EVs integrated with 17 smart BIPVs show that the strategy effectively optimizes the usage of the energy produced by the PV units to charge the EVs, contributes to reduce non-renewable energy consumption of the building sector, and satisfies the EV owners' energy requirements for transportation.
Keywords: Aggregator; building integrated photovoltaic; electric vehicles; green energy index; local energy market; smart charging